Stress distribution around osseointegrated implants with different internal-cone connections: photoelastic and finite element analysis - Anami, Lilian Costa [UNESP]; Costa Lima, Julia Magalhaes da [UNESP]; Takahashi, Fernando Eidi [UNESP]; Neisser, Maximiliano Piero [UNESP]; Noritomi, Pedro Yoshito; Bottino, Marco Antonio [UNESP] (Allen Press Inc, 2015)
The goal of this study was to evaluate the distribution of stresses generated around implants with different internal-cone abutments by photoelastic (PA) and finite element analysis (FEA). For FEA, implant and abutments with different internal-cone connections (H- hexagonal and S- solid) were scanned, 3D meshes were modeled and objects were loaded with computer software. Trabecular and cortical bones and photoelastic resin blocks were simulated. The PA was performed with photoelastic resin blocks where implants were included and different abutments were bolted. Specimens were observed in the circular polariscope with the application device attached, where loads were applied on same conditions as FEA. FEA images showed very similar stress distribution between two models with different abutments. Differences were observed between stress distribution in bone and resin blocks; PA images resembled those obtained on resin block FEA. PA images were also quantitatively analyzed by comparing the values assigned to fringes. It was observed that S abutment distributes loads more evenly to bone adjacent to an implant when compared to H abutment, for both analysis methods used. It was observed that the PA has generated very similar results to those obtained in FEA with the resin block.
Keywords: Internal-cone connections; Finite element analysis; Photoelasticity